Use of adherent additives in designing asphalt hot mixtures: a review (Gaceta Técnica, 2021)
Considering the need to guarantee a useful and durable life of road surfaces, the development of new materials has been generated that ensure the adherence between bitumen and aggregates, being able to combat the failure caused by humidity. In this literary review, different scientific articles were analyzed in order to determine the performance of the different adherents used in hot asphalt mixes, the optimal percentages, and the different methods used to find resistance to moisture. It was found that the different adherent additives, both natural and chemical, show exceptional performance against moisture resistance, providing a long-lasting useful life for the pavement, in different optimal percentages that vary according to the aggregate used in the mixture. The most widely used methods to determine moisture resistance were the pull-out test, Vialit adhesion, modified Lottman test, and boiling water test
Keywords: asphalt mix; moisture damage; adherent additives; cracking from fatigue